2017
DOI: 10.1111/bph.13732
|View full text |Cite
|
Sign up to set email alerts
|

Exercise effects on perivascular adipose tissue: endocrine and paracrine determinants of vascular function

Abstract: Obesity is a global epidemic, accompanied by increased risk of type 2 diabetes and cardiovascular disease. Adipose tissue hypertrophy is associated with adipose tissue inflammation, which alters the secretion of adipose tissue‐derived bioactive products, known as adipokines. Adipokines determine vessel wall properties such as smooth muscle tone and vessel wall inflammation. Exercise is a mainstay of prevention of chronic, non‐communicable diseases, type 2 diabetes and cardiovascular disease in particular. Asid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 152 publications
1
41
0
1
Order By: Relevance
“…Also AT expresses FGF21 which might be implicated in CVD since it is associated with cardio-metabolic risk factors, increased intima-media thickness of carotid and iliac arteries, high levels of C-reactive protein, dysglycemia, dyslipidemia, and decreased adiponectin levels (129,130). As for IL-6, the existence of different tissue sources of FGF21 suggests tissue-specific physiological functions (131).…”
Section: Fibroblast Growth Factor 2 (Fgf2) and Fgf21mentioning
confidence: 99%
“…Also AT expresses FGF21 which might be implicated in CVD since it is associated with cardio-metabolic risk factors, increased intima-media thickness of carotid and iliac arteries, high levels of C-reactive protein, dysglycemia, dyslipidemia, and decreased adiponectin levels (129,130). As for IL-6, the existence of different tissue sources of FGF21 suggests tissue-specific physiological functions (131).…”
Section: Fibroblast Growth Factor 2 (Fgf2) and Fgf21mentioning
confidence: 99%
“…which poses a great challenge to human health. 12,13 Accompanying obesity, the crosstalk between adipose and cancer-prone cells may occur via obesity-associated hormones, cytokines and other mediators and finally results in increased cancer risk and/or progression, 14 which has started to gather more and more attention. 15,16 For example, Wolin et al reported that 20% of cancer patients was attributable to excess body weight.…”
mentioning
confidence: 99%
“…Also, utilizing the PVAT FAI may help to assess the efficacy of novel therapeutics to inhibit vascular inflammation and improve cardiovascular mortality and morbidity. Furthermore, studies in mice suggest that exercise and brown adipocyte inducers such as cold exposure and pharmacological β-adrenergic stimulation can enhance the protective effects of PVAT on vascular function through PVAT browning [51,52]. While this is an attractive potential strategy to improve PVAT function, more studies are required to understand the therapeutic implications and to validate these findings in humans.…”
Section: Discussionmentioning
confidence: 99%